2011
DOI: 10.1007/s10552-011-9882-9
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy, genetic polymorphisms of metabolic enzymes, and childhood acute leukemia: the ESCALE Study (SFCE)

Abstract: The ESCALE study did not evidence the interaction between CYP1A1*2A/2B and maternal smoking suggested previously. The association with NAT2*5 and the gene-gene interactions need to be replicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 61 publications
(60 reference statements)
1
34
0
Order By: Relevance
“…In total there were 26 unique SNPs corresponding to 14 unique genes. The genes ABCC1 (rs8187858, FET, P = 0.001 [32], cds-synon), CHST3 (rs4148943, FET, P = 0.002, UTR-3), ABCC4 (rs4148551, FET, P = 0.01, UTR-3), CYP2E1 (rs3813867, FET, P = 0.01 [33,34], nearGene-5), and ALDH3A1 (rs887241, FET, P = 0.01, missense [35]) were among the most significant hits. Of the 14 genes identified, three are from the ABCC family (ABCC1, ABCC4, ABCC6), and two are from the CHST family (CHST3, CHST13).…”
Section: Snp Comparative Analysis Of Gemcitabine Responsementioning
confidence: 99%
“…In total there were 26 unique SNPs corresponding to 14 unique genes. The genes ABCC1 (rs8187858, FET, P = 0.001 [32], cds-synon), CHST3 (rs4148943, FET, P = 0.002, UTR-3), ABCC4 (rs4148551, FET, P = 0.01, UTR-3), CYP2E1 (rs3813867, FET, P = 0.01 [33,34], nearGene-5), and ALDH3A1 (rs887241, FET, P = 0.01, missense [35]) were among the most significant hits. Of the 14 genes identified, three are from the ABCC family (ABCC1, ABCC4, ABCC6), and two are from the CHST family (CHST3, CHST13).…”
Section: Snp Comparative Analysis Of Gemcitabine Responsementioning
confidence: 99%
“…Genetic susceptibility to childhood ALL 9 (rs3813867/rs2031920), is provided by a meta-analysis of four studies showing a strong increased risk (dominant: OR = 1.99, 95 % CI 1.32-3.00), and one of two additional studies reported results in a consistent direction [16,49]. Regarding other phase I metabolism genes previously examined, available evidence has been less consistent for the CYP2D6, CYP3A5, and epoxide hydrolase 1 (EPHX1) genes.…”
Section: Xenobiotic Metabolism and Transportmentioning
confidence: 99%
“…Meta-analyses of two variants in CYP2D6, G1934A (rs3892097) and del2637 (rs35742686) [12], each based on results from three studies, show weak evidence of an association, which is reinforced by inconclusive results in a recent study [50] (Table 2). Statistically significant risk estimates have been reported in both directions for CYP3A5 G6986A (rs776746) [16,[51][52][53] and EPHX1 T339C (rs1051740) [16,49,50,54,55], and four studies evaluating EPHX1 A418G (rs2234922) have shown largely non-significant results [49,50,54,55].…”
Section: Xenobiotic Metabolism and Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that the interaction between these genes and environmental factors may also affect the susceptibility to leukemia [10]- [12]. Microsomal epoxide hydrolase (EPHX1), along with CYP, another family of xenobiotic-metabolizing enzymes, plays an important role in both the detoxification and activation of procarcinogens [13] [14] and is considered to be a protective enzyme [15].…”
Section: Introductionmentioning
confidence: 99%